Laparo-Endoscopic Single Site Combined With Hysteroscopy to Diagnose and Treat Robert’s Uterine Malformation: A Case Report - Hong, Xin-Yi; Ding, Bo; Shen, Yang (Frontiers in Surgery, 2022)
Asymmetric septate uterus, commonly known as Robert’s uterus, is an exceedingly rare uterine malformation described for the first time in 1970 by Robert H. Currently, surgery is the therapy of choice for Robert’s uterus, with surgical choices ranging from laparotomy to minimally invasive surgery. In this paper, we reported that a 14-year-old girl with primary dysmenorrhea that gradually worsened three months after menarche had surgery after many imaging evaluations, and that the intraoperative diagnosis was Robert’s uterus. The diagnostic and therapeutic laparo-endoscopic single site(LESS) combined with hysteroscopy surgery for Robert’s uterine abnormality was shown via a step-by-step presentation of the method accompanied by narrated video footage. During the ten-month postoperative follow-up period, the patient had monthly recurrences with normal menstrual volume and no dysmenorrhea, demonstrating that as a minimally invasive treatment, LESS combined with hysteroscopy surgery is a successful methodfor diagnosing and treating this specific malformation.